Anatomical variations and bilateral symmetry of roots and root canal system of mandibular first permanent molars in Saudi Arabian population utilizing cone- beam computed tomography - Mohammed Mashyakhy; Hemant Ramesh Chourasia; Esam Halboub; Abeer Abdulkareem Almashraqi; Yahia Khubrani; Gianluca Gambarini (Elsevier, 2019)
Aim: The aim of the study was to evaluate the anatomical variations of the roots and root canal system, and to determine the symmetry between right and left sides of mandibular first permanent molars in Saudi Arabian population using images derived from cone beam computed tomography (CBCT) scans. Methods: The CBCT scans (with the following parameters: FOV 170 × 120 mm, 90 Kv, 5-8 mA, 17.5 s exposure time and 0.25 mm voxel size) were retrieved from the database and axial, coronal and sagittal sections of mandibular first molars were examined. The number of roots, canals and type of canal configuration based on Vertucci's classification were recorded. Bilateral symmetry between right and left side of the same individuals and differences between genders were investigated. Results: Out of 174 mandibular first molars, 97.1% were two rooted and 2.9% were three rooted (distolingual root). In regards to the number of canals, 73% had three, 25.3% had four and 1.7% had two root canals. In teeth with four root canals, 90.9% of the extra canal was in the distal root, while 9.1% in the extra distolingual root. The most common canal configuration in mesial and distal root were type IV (64.9%) and type I (77%), respectively. Symmetrical analysis revealed 100% symmetry in number of roots and 56.4% in number of canals between right and left teeth in the same individual. Conclusions: Within the limitation of this study, wide range of canals configurations were noted in mandibular first molars among the Saudi Arabian population. The prevalence of three rooted mandibular first molars was relatively low. Three canals were most commonly seen in mandibular first molars. Bilateral symmetry was varied in number of canals and canals configurations, which could be of clinical significance while performing root canal treatment on both side mandibular first permanent molars. Keywords: Cone beam computed tomography, Mandibular first molar, Root canal, Saudi Arabian